Meta Analysis of Morphological Charteristics of Local Durian (Durio SPP) - Hajar Setyaji; Metha Monica (Jurnal Info Sains : Informatika dan Sains, 2024)
The durian plant is a native Indonesian plant that produces fruit that is very popular with the public because of its distinctive taste, aroma and texture of the pulp. The high demand for superior durian fruit is a challenge because of the high variation in the quality of durian fruit. The meta-analysis of the morphological character of durian plants aims to provide an overview of the distribution of the morphological study of local durian plants. The research method was carried out by conducting research on the morphology of durian plants using the keyword google search engine by limiting it to journals written by Indonesians, selecting, and extracting related morphological parameters and analyzing them qualitatively. The results of the study showed that the morphology of durian fruit received the first priority, followed by durian leaves and seeds. Conclusion The morphology of local durian plants as a first step in finding superior durian seedlings still shows the diversity of measurements of morphological characteristics.